Application of the Levenberg-Marquardt method to the training of spiking neural networks - Silva, S. M. (2013)
One of the basic aspects of some neural networks is their attempt to approximate as much as possible their biological counterparts. The goal is to achieve a simple and robust network, easy to comprehend and capable of simulating the human brain at a computational level. This paper presents improvements to the Spikepro algoritm, by introduting a new encoding scheme, and illustrates the application of the Levenberg Marquardt algorithm to this third generation of neural network.